
2a^2  3a = 5.
2a^2  3a  5 = 0,
Use the AC Method:
A*C = 2*(5) = 10,
2a^2 + (2a  5a) 5 = 0,
Group the 4 terms into 2 factorable pairs:
(2a^2 + 2a) + (5a  5) = 0,
Factor each binomial:
2a(a + 1) 5(a + 1) = 0,
Factor out a+1:
(a + 1)(2a  5) = 0,
a + 1 = 0,
a = 1.
2a  5 = 0,
2a = 5,
a = 2.5.
Solution set: a = 1, and a = 2.5.
posted by Henry
Respond to this Question
Similar Questions

biology
Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner? −O−−−H −C−H−− −N−−−H 
linear algebra
solve using gauss jordan 10y − 4z + w = 1 x + 4y − z + w = 2 3x + 2y + z + 2w = 5 −2x − 8y + 2z − 2w = −4 x − 6y + 3z = 1 
calculus
Find an equation for the surface consisting of all points P(x, y, z) equidistant from the point P(0, 1, 0) and the plane x = 3. Answer Choices: 1. y2 + z2 − 6x + 2y − 8 = 0 2. x2 + z2 + 6y − 2z − 8 = 0 3. 
Grade 12 Calculus
Evaluate each of the following. Show all your calculations. a) f'(3) if f(x) = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X) = −3x^2 − 5x + 7 
algebra or algebra1
What is the set of all values of x for which the expression x + 6 /x2 −2x−8 is not deﬁned? A) {−6,−4,2} B) {−6,−2,4} C) {−4,2} D) {−2,4} E) {−6} 
algebra help!!!!
Add: b^−3 ca^−1 −xc^−2 how would i do this ? Let me make sure I have the question right. We have b^(−3) ca(^−1) −xc^(−2 )=? You might also write this as (1/b^3) c(1/a) − 
calculus (gr 12)
Evaluate each of the following. Show all your calculations. a) f'(3) if f(x) = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X) = −3x^2 − 5x + 7 
calculus (gr 12)
Evaluate each of the following. Show all your calculations. a) f'(3) if f(x) = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X) = −3x^2 − 5x + 7 
physics
Four charges −8 × 10^−9 C at (0 m, 0 m), −7 × 10^−9 C at (5 m, 1 m), −1 × 10^−9 C at (−2 m, −3 m), and 2 × 10^−9 C at (−2 m, 4 m), are arranged in the (x, y) plane as 
algebra
Which of the following is equivalent to the expression (t2 − t − 6)(t − 3)−1 ? a. t3 − 9t +18 b. (t − 2)(t + 3) c. (t + 2)(t − 3) d. (t − 2) e. (t + 2)this is the answer how is the